Molar Ratio Comparison of Ti-Zr as Catalyst Support of Bentonite in Esterification Reaction - Firmansyah, Sanji; Agustian, Egi; Rinaldi, Nino; Widiarti, Nuni; Hanifah, Yuliza; Maisaroh, Maisaroh; Sulaswatty, Anny (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Natural bentonite from Pacitan - Indonesia as a support in the preparation of Ti and Zr-pillared metal catalysts (Ti-Zr/bent) for esterification reaction were studied. The preparation of Ti-Zr/bent catalyst was prepared to find out the effect of molar ratios (Ti:Zr) where an investigation was performed in the esterification of waste cooking oil. The catalyst was varied as follows: 0.5:1 (Ti-Zr-1/bent), 1:1 (Ti-Zr-2/bent), 1.5:1 (Ti-Zr-3/bent), 2:1 (Ti-Zr-4/bent), and 5:1 (Ti-Zr-5/bent) were used to determine the yield. The reaction was carried out for 3 hours at 150°C and a pressure of 40 bar N2 gasses. The result of the Ti-Zr/bent catalyst was given increasing significantly for surface area of 133–147 m²/g compares to bentonite 27 m²/g and 10 times of acidity. The best catalyst was shown in 2:1 of ratio Ti:Zr (molar) on esterification reaction with succesfuly performed about 80.40% of yield. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).